2019
DOI: 10.1055/s-0039-1694969
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices and Risk of Death and Cardiovascular Events: Results from a Large Population-Based Cohort Study

Abstract: Studies evaluating the relationship between platelet indices and cardiovascular (CV) outcomes yielded conflicting results. We assessed the incidence of adverse events according to baseline quintiles of platelet indices in the prospective cohort of the Malmö Diet and Cancer Study. A total of 30,314 individuals (age 57 ± 8 years) were followed for a median of 16 years (468,490 person-years). Outcome measures included all-cause death, CV death, myocardial infarction (MI), and ischemic stroke. The fifth quintile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…PLR is a simple inflammatory marker that does not need any additional laboratory testing, and easily calculated by the platelet count/lymphocyte count formula. According to several population-based cohort studies, increased platelet counts had a significant association with mortality, risk of cardiovascular disease, and dementia [24][25][26]. In patients with hip fracture, Galivanche et al [27] reported that high platelet counts were a risk factor for developing a post-operative pressure ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…PLR is a simple inflammatory marker that does not need any additional laboratory testing, and easily calculated by the platelet count/lymphocyte count formula. According to several population-based cohort studies, increased platelet counts had a significant association with mortality, risk of cardiovascular disease, and dementia [24][25][26]. In patients with hip fracture, Galivanche et al [27] reported that high platelet counts were a risk factor for developing a post-operative pressure ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there are no randomized trial data on the effects of exogenous testosterone on circulating leukocytes and platelets. Because of the known association of increased leukocyte [15][16][17][18] and platelet counts [19][20][21] with cardiovascular and thromboembolic risk, these findings, if confirmed in human studies, could affect the safety of testosterone treatment. These findings could also provide important clues to the site of testosterone's action in the bone marrow.…”
Section: Suppression Of Endogenous Testosterone Secretion Throughmentioning
confidence: 93%
“…The findings of increased platelet count observed in the 5aR should be further evaluated in larger trials because higher platelet counts, even within the normal range, are associated with an increased risk of ischemic stroke, and cardiovascular and all-cause death. [19][20][21] Increased platelet counts are associated with risk of venous thromboembolism during recovery from acute illness and in cancer patients. 35 This study has several strengths and some limitations.…”
Section: Ta B L Ementioning
confidence: 99%
“…Finally, the long‐term risk of cardiovascular morbidity and mortality may not be associated with MPV. Recently, Patti et al found the risk of adverse cardiovascular events similar across different MPV quintiles 113 …”
Section: How Does Platelet Size Change In Disease?mentioning
confidence: 99%